Prehensile: an explication of this is Africa, a travel memoir by Jack Rathmell - Rathmell, John (Centre for Film and Media Studies, 2025)
“Prehensile” is a 10,000 word explication analyzing T.I.A, a travel memoir by Jack Rathmell (the candidate). Prehensile examines the various philosophical themes running throughout the book, as well as addressing the ethical dilemmas and other problems the Western world faces as regards the outside world. The explication will also attempt a degree of meta-analysis, discussing the process by which art and self-expression takes place in the modern world; the process by which,in this case, a book goes from a mere idea to a physical product, and what it takes to market such an idea in today's world, in which the lines between “individual” and “brand” have blurred; to this end, both a website and a physical, hand-bound copy of the book have been designed and created for this project, and will be provided for examination. (The pdf of the book has also been appended to the thesis.) Here is the introduction of Prehensile: 1. Introduction Primarily, TIA is a book about struggling to find a place in the modern world. It is a book about the status quo, and our navigation of its systems it uses to maintain social, political, and economic control. The story is told with South Africa as a backdrop; my three visits (totaling two years) to the country are covered, taking place over roughly five years. The first stint took place as a 19-year-old volunteer, which situates many of the issues discussed below. These topics include the malaise, the paralysis by (white) guilt that so many visitors feel. Nevertheless, the memoir being set in South Africa is largely incidental. The emotional connection and sentimentality I developed with and for South Africa is presented as a chance byproduct; it could, I suggest, just as likely have been Thailand or Guatemala that catalyzed my reflections and personal growth. This realization comes as a result of reflecting on how we relay our stories, what mobilizes us to act, and just how influential luck is in shaping our existence. There are also more existential questions at play. In a world where, increasingly, day to day existence is being commodified, and our privacy and personal sovereignty are being encroached upon, we (in the West) are forced non-consenting into a perpetual state of performance and spectacle (Adorno & Bernstein, 2015). At all times we are at once being surveilled and surveilling others (Zuboff, 2020). The way we perceive ourselves and the outside world has been co-opted, and is thus constantly in flux at both the individual and societal level. As a result of these forces (the deluge of targeted marketing, cynical media, and corporate propaganda), reality, truth, and perception are more subjective than ever before. A pertinent example of this is the potential for TIA's publishing, and the modern day requirements for this process, including creating an online presence and offering a curated version of myself for public inspection. Even art and self expression requires conformity and participation in these norms; I am forced to design and construct a curated version of myself through the lens of how I would like to be perceived by the outside world. The lines between individual and brand have become blurred. Subjective Realism is another recurring topic. Our warped perceptions can be especially problematic regarding places that have been victims of colonialism and imperialism; traveling Westerners now “inflict” our subjective realities on these other places and peoples. At the same time, travel - even “non-traditional” travel - has been commodified, thus homogenized and controlled. To travel requires an arduous navigation of various bureaucratic minutiae and lethargy; a signing-away of one's privacy and agency to these actors, at least for a time. Even if you are able to pass these hurdles, these “exotic” places have also been tampered with. Therefore, the commodification of adventure is another topic of interest: can there be genuine discovery, exploration, or “Wanderlust” today? The theme of “prehensility” also appears repeatedly. Much of the memoir is a personal struggle: reaching for meaning in culture, experience, social interaction, and memory. These attempts are often futile, but prove fruitful - or at least thought-provoking - on occasion. The book mostly takes place in South Africa, but the tonality of the writing and the nature of the content suggests that the setting is largely immaterial as it relates to my perceptions, neuroses, and insecurities. Chiefly, the location serves only to provide me with various latching on points onto which I can briefly reflect on whatever issues are at hand. I use the locale as a foil against which I can relativize the sociocultural and political observations I have made at home in the US. Social hierarchies - explicit or otherwise - are another theme. One of the more memorable examples relates to my interactions with a group of French exchange students I met during my second trip to South Africa. They came to South Africa under the guise of hoping to improve their English, as well as to connect with a foreign country. Neither of these objectives were fulfilled, and the social ecosystem devolves into a series of increasingly bizarre interactions. Their biases, insecurities, and misconceptions ensure that their perception of both me and the country we are visiting will be obfuscated. Further instances of insularity are discussed in the memoir, leading the author (and reader) into a deeper examination of what travel, charity, and guilt are able to achieve, especially in terms of our biases shaping our experiences and interactions with those whom we believe to be below us on our imaginary social ranking. By inserting ourselves into these complex situations armed only with our saviour complexes, we become caricatures. By focusing too much on cultural differences and negative emotion we risk driving the wedge of division further. Indeed, our appetite to right historical wrongs can be patronizing and can serve to perpetuate unhelpful norms and beliefs. These ethical dilemmas are repeatedly referenced; Westerners' inability to find the proper lens through which we can view our experiences in these exotic locales. The thin line between cultural appreciation and appropriation is one that has been barreled through by countless well-meaning actors; the memoir reflects on this ongoing debate.